Environmental Policy Strategy and Law Enforcement of Peatland Fires: An Environmental Law Perspective - M. Iqbal; Sujianto Sujianto; Erdianto Erdianto; Daeng Ayub; Adinan Yahring (APPTHI, 2023)
Abstract. Peatland fires have immensely contributed to environmental degradation, climate change, and health problems in Indonesia. This research article seeks to understand the environmental policy, strategy, and law enforcement mechanisms applied in Riau, Indonesia to reduce greenhouse gas emissions arising from peatland fires. Using a qualitative approach incorporating normative juridical strategies and empirical research data, this study analyzes the institutional framework, existing policies and strategies, and legal mechanisms that have been adopted in Riau, Indonesia to reduce greenhouse gas emissions. The study reveals that Indonesia has put in place a robust institutional framework comprising government agencies and non-governmental organizations tasked with the responsibility of conducting research on peatland fires, and implementing programs and policies aimed at reducing the effects of these fires. Moreover, the study shows that existing environmental policies and strategies, including national, regional, and local regulations, have been instrumental in preventing peatland fires and sustaining eco-friendly practices in Riau. The study concludes by recommending the need for stronger law enforcement, institutional capacity building, and stakeholder involvement to improve the effectiveness of environmental policies and strategies in reducing greenhouse gas emissions. Keywords: Peatland, Environmental policy, Law enforcement, Greenhouse gas emissions, Eco-friendly practices Abstrak. Kebakaran lahan gambut telah memberikan kontribusi besar terhadap degradasi lingkungan, perubahan iklim, dan masalah kesehatan di Indonesia. Artikel penelitian ini berupaya memahami kebijakan lingkungan, strategi, dan mekanisme penegakan hukum yang diterapkan di Riau, Indonesia untuk mengurangi emisi gas rumah kaca yang timbul dari kebakaran lahan gambut. Dengan menggunakan pendekatan kualitatif yang menggabungkan strategi yuridis normatif dan data penelitian empiris, penelitian ini menganalisis kerangka kelembagaan, kebijakan dan strategi yang ada, serta mekanisme hukum yang telah diadopsi di Riau, Indonesia untuk mengurangi emisi gas rumah kaca. Studi ini mengungkapkan bahwa Indonesia telah memiliki kerangka kelembagaan yang kuat yang terdiri dari lembaga pemerintah dan organisasi non-pemerintah yang diberi tanggung jawab melakukan penelitian mengenai kebakaran lahan gambut, dan melaksanakan program dan kebijakan yang bertujuan untuk mengurangi dampak kebakaran tersebut. Selain itu, penelitian ini menunjukkan bahwa kebijakan dan strategi lingkungan hidup yang ada, termasuk peraturan nasional, regional, dan lokal, telah berperan penting dalam mencegah kebakaran lahan gambut dan mempertahankan praktik ramah lingkungan di Riau. Studi ini menyimpulkan dengan merekomendasikan perlunya penegakan hukum yang lebih kuat, peningkatan kapasitas kelembagaan, dan keterlibatan pemangku kepentingan untuk meningkatkan efektivitas kebijakan dan strategi lingkungan dalam mengurangi emisi gas rumah kaca. Kata kunci: Lahan gambut, Kebijakan lingkungan, Penegakan hukum, Emisi gas rumah kaca, Praktik ramah lingkungan